2018
DOI: 10.1155/2018/2836389
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing Alpha-1 MZ Individuals Shows Frequent Biallelic Mutations

Abstract: Rationale Individuals with a single Z mutation in the SERPINA1 gene that codes for alpha-1 antitrypsin (AAT) are at increased risk for COPD if they have ever-smoked. Whether additional variants alter the risk for COPD in this population remains unknown. Objectives To determine whether additional SERPINA1 variants impact COPD development in a previously identified MZ (carrier) cohort. Methods Individuals with prior MZ results and AAT serum level <16uM were recruited from the Alpha-1 Coded Testing study and Alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The normal allele is referred to as "M." The critical variant is the "Z" allele that causes AAT deficiency by homozygous substitution of glutamic acid by lysine at position 342 (Glu342Lys) [ 3 ]. AAT is a protease inhibitor, denoted as "PI" [ 4 ]. The alleles are denoted with related letters.…”
Section: Discussionmentioning
confidence: 99%
“…The normal allele is referred to as "M." The critical variant is the "Z" allele that causes AAT deficiency by homozygous substitution of glutamic acid by lysine at position 342 (Glu342Lys) [ 3 ]. AAT is a protease inhibitor, denoted as "PI" [ 4 ]. The alleles are denoted with related letters.…”
Section: Discussionmentioning
confidence: 99%
“…As such, many PI*MZ individuals with lower AAT levels and COPD may, in fact, be compound heterozygotes for the Z allele and a rare/M-like allele [ 59 ]. A recent study has reported a high rate of rare deficiency alleles in individuals who were previously identified as PI*MZ [ 60 ], which raises the question of what proportion of PI*MZ patients with severe disease/fast decline are ‘true’ PI*MZs. The challenges to accurately diagnosing rare/M-like Z compound heterozygotes include a lack of awareness and ability to detect rare alleles (e.g., with gene sequencing).…”
Section: Discussionmentioning
confidence: 99%
“…These findings need to be evaluated in larger cohorts with sequencing but justifies the sequencing of SERPINA1 in a subgroup of at-risk smokers with COPD, emphysema, and low alpha-1 antitrypsin concentrations in the absence of two pathogenic SNPs covered by chip genotyping panels. Commercial testing kits already perform resequencing in those with alpha-1 antitrypsin deficiency if SERPINA1 panel genotyping is negative (45). A similar, step-wise approach for CFTR resequencing is standard for individuals with clinical features of cystic fibrosis and elevated sweat chloride concentrations despite negative CFTR panel genotyping (46).…”
Section: Discussionmentioning
confidence: 99%